Studi Analisis Ijtihad Rasul SAW dalam Kitab Ijtihad Rasul SAW - Muhammad Ihwan (Program Pascasarjana Universitas Ibrahimy, 2018)
This research aims to find out the views of the scholars about the ijtihad of the Prophets in the book of Ijtihad al-Rasul SAW by Abdul Jalil Isa and to find out the description of the actions of the Prophet Muhammad which was considered ijtihad. The type of research is used by qualitative research. The data obtained were clarified and analyzed according to the topic of discussion. From the results of the data collection and analysis can be concluded that are: 1) The Preception of the scholars about ijtihad of the Prophets in the book of Ijtihad al-Rasul SAW are divided into three. Firstly, Abu Ali al-Juba'i argued that the Prophet did not carry out jihad, both in legal matters (sharia) and worldly affairs in. Secondly, Ibn Hazm, Ibn Taymiyyah and Kamal al-Hummam argued that the Prophet had jihad, both in the affairs of the Shariah and world affairs in. Thirdly, Qadhi Iyadh and Ibn Khaldun argued that the Prophet did not carry out jihad in the Shari'ah region, the Prophet only had jihad the in area of world affairs. This difference of opinions are based on the third approach in concluding the Prophet's ijtihad; 2) The act of the Prophet Muhammad SAW which was considered ijtihad in the book of Ijtihad al-Rasul SAW was that there were two, namely: The first, the act which turned out to be wrong then by the Shari was straightened out, and secondly, his decision was not followed by his friend.